RIVER BANK PROTECTION PLANNING IN ATIROMPE VILLAGE, MAJALAYA SUB DISTRICT, MAJALAYA DISTRICT, BANDUNG REGENCY - Rodiah, Siti
Majalaya District is one of the areas in Bandung Regency, which is passed by the Citarum River with springs at Situ Cisanti. Water from Situ Cisanti flows into the Majalaya area through a steep slope from an altitude of ±1500 m above sea level down to a height of ±700 m. It causes the flow of the river around Majalaya to have a higher speed and energy than the area after. Hence, the river bank around Majalaya also has a higher potential to experience scouring, especially at the outer bend of the river. In order to handle river bank scouring in Atirompe Village, Majalaya Village, Majalaya District, Bandung Regency, along the 325 meters, which is right on the outer bend of the Citarum River, technical planning for river bank protection is needed. Hydraulic modeling with HEC-RAS 6.2 was carried out to obtain the magnitude of the flood water level elevation, flow velocity, and the potential for scouring that occurred as the basis for the preparation of the solution. Considering the results of the simulation of flood discharge for a return period of 25 years and the potential for scouring, a retaining walls with a height of 10 meters was chosen to protect the river bank in Atirompe Village from the risk of scouring.